Cost‐effective molecular inversion probe‐based ABCA4 sequencing reveals deep‐intronic variants in Stargardt disease. Issue 10 (18th June 2019) - Khan, Mubeen; Cornelis, Stéphanie S.; Khan, Muhammad Imran; Elmelik, Duaa; Manders, Eline; Bakker, Sem; Derks, Ronny; Neveling, Kornelia; van de Vorst, Maartje; Gilissen, Christian; Meunier, Isabelle; Defoort, Sabine; et al.
Abstract: Purpose: Stargardt disease (STGD1) is caused by biallelic mutations in ABCA4, but many patients are genetically unsolved due to insensitive mutation‐scanning methods. We aimed to develop a cost‐effective sequencing method for ABCA4 exons and regions carrying known causal deep‐intronic variants. Methods: Fifty exons and 12 regions containing 14 deep‐intronic variants of ABCA4 were sequenced using double‐tiled single molecule Molecular Inversion Probe (smMIP)‐based next‐generation sequencing. DNAs of 16 STGD1 cases carrying 29 ABCA4 alleles and of four healthy persons were sequenced using 483 smMIPs. Thereafter, DNAs of 411 STGD1 cases with one or no ABCA4 variant were sequenced. The effect of novel noncoding variants on splicing was analyzed using in vitro splice assays. Results: Thirty‐four ABCA4 variants previously identified in 16 STGD1 cases were reliably identified. In 155/411 probands (38%), two causal variants were identified. We identified 11 deep‐intronic variants present in 62 alleles. Two known and two new noncanonical splice site variants showed splice defects, and one novel deep‐intronic variant (c.4539+2065C>G) resulted in a 170‐nt mRNA pseudoexon insertion (p.[Arg1514Lysfs*35, =]). Conclusions: smMIPs‐based sequence analysis of coding and selected noncoding regions of ABCA4 enabled cost‐effective mutation detection in STGD1 cases in previously unsolved cases.